2020
DOI: 10.3390/foods9030298
|View full text |Cite
|
Sign up to set email alerts
|

Water Cooking Stability of Dried Noodles Enriched with Different Particle Size and Concentration Green Tea Powders

Abstract: Incorporating green tea powder (GTP) into dried noodles enriched the functional characteristics of noodles. To achieve the maximum benefits from GTP, the water cooking stability of dried green tea noodles (DGTN) should be investigated. Indeed, antioxidant activities and phenolic compounds of DGTN after water cooking markedly decreased. The results showed that large GTP particles caused the increased cooking loss of DGTN, but the phenolic compound loss of DGTN prepared with them was low after cooking. Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
2
8
1
Order By: Relevance
“…However, due to the lower concentration of gluten in GBP, the stability of the interaction of starch to the gluten network was decreased, which resulted in the higher cooking loss and larger size of holes in cooked noodles. Similar results were obtained from other studies [ 24 , 50 ].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…However, due to the lower concentration of gluten in GBP, the stability of the interaction of starch to the gluten network was decreased, which resulted in the higher cooking loss and larger size of holes in cooked noodles. Similar results were obtained from other studies [ 24 , 50 ].…”
Section: Resultssupporting
confidence: 92%
“…Cooking loss not only reflects the solid content lost to cooking water during the cooking time, but also represents chimerism between starch and protein, and the integrity of the noodle network structure [ 24 ]. As shown in Table 6 , when the GBP concentration was increased from 0% to 40%, the cooking loss increased gradually, rising from 4.10% to 11.20%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be remembered that the size of this parameter is influenced, among others, by the specific surface of the pasta (shape and size of pasta) as well as specificity of the raw material (particle size, degree of starch damage) and their chemical composition. Yu et al [27] indicated that larger particles of green tea powder introduced into noodles had the effect of increasing the loss of dry matter while cooking pasta. Moreover, the shape and form of pasta also influence the stability of the product during the cooking process.…”
Section: Cooking Qualitymentioning
confidence: 99%
“…At the same time, as the addition of tea extract increased from 0.0 to 2.0%, the total phenolic content of noodles, 1,1-diphenyl-2-picryl hydrazyl (DPPH) free radical clearance activity, and resistant starch content increased. Research on the water cooking stability of dried noodles enriched with different particle sizes and concentrations of green tea powders by Yu et al [ 11 ] found that the antioxidant activity and phenolic compounds of dry green tea noodles decreased significantly after water cooking. The results showed that large green tea granules increased the cooking loss of green tea noodles, but the phenolic compounds of dry green tea noodles prepared with them were lost after cooking.…”
Section: Introductionmentioning
confidence: 99%